2019
DOI: 10.1002/ecy.2920
|View full text |Cite
|
Sign up to set email alerts
|

Positive interspecific associations consistent with social information use shape juvenile fish assemblages

Abstract: Danylchuk. 2020. Positive interspecific associations consistent with social information use shape juvenile fish assemblages. Ecology 101(2):

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 139 publications
0
15
0
Order By: Relevance
“…Information and its use in animals is an important topic in behaviour, ecology, and evolution because information is a critical currency that allows animals to make adaptive decisions in a given situation (e.g., Dall et al, 2005; Danchin et al, 2004; Hoppitt & Laland, 2013; Rieucau & Giraldau, 2011). The decision of when to utilize social versus private information to best exploit potential opportunities while avoiding costs is crucial for success and has been studied within a variety of both social and nonsocial animals (e.g., Bonnie & Earley, 2007; Grüter & Ratnieks, 2011; Haak et al, 2020; Taborsky & Oliveira, 2012; Weimerskirch et al, 2010; Wray et al, 2012). However, it is still unclear whether and how molecular and neurosensory factors determine an individual's preference for social or private information.…”
Section: Discussionmentioning
confidence: 99%
“…Information and its use in animals is an important topic in behaviour, ecology, and evolution because information is a critical currency that allows animals to make adaptive decisions in a given situation (e.g., Dall et al, 2005; Danchin et al, 2004; Hoppitt & Laland, 2013; Rieucau & Giraldau, 2011). The decision of when to utilize social versus private information to best exploit potential opportunities while avoiding costs is crucial for success and has been studied within a variety of both social and nonsocial animals (e.g., Bonnie & Earley, 2007; Grüter & Ratnieks, 2011; Haak et al, 2020; Taborsky & Oliveira, 2012; Weimerskirch et al, 2010; Wray et al, 2012). However, it is still unclear whether and how molecular and neurosensory factors determine an individual's preference for social or private information.…”
Section: Discussionmentioning
confidence: 99%
“…A dominance of positive correlations was also obvious for the piscivorous pikeperch in the p/a dataset of our study, supporting the results from the Ontario lakes (MacDougall et al., 2018) that the occurrence of predators might profit from an increase in prey numbers. Additionally, it has been suggested that positive interspecific interactions between species might emerge from the shared use of social information in juvenile fish communities (Haak et al., 2020). In our dataset, positive correlations were often found between species of the same family (Cyprinidae), which is the most species‐rich fish family in European lakes (Kottelat & Freyhof, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, co‐occurrence of closely related species remains a paradox because classic interspecific competition theory predicts that niche conservatism is responsible for high niche overlap between such species, but this overlap should prevent their coexistence (Harper et al 1961, MacArthur and Levins 1967). Moving away from a focus on competition, recent work has highlighted that positive interactions can also contribute to assembly of closely related flocking species, such as facilitation in mixed‐species bird flocks (hereafter, “flocks,” Goodale et al 2010), Müllerian mimicry rings of butterflies (Elias et al 2008), and heterospecific groups of juvenile fish (Haak et al 2019). Indeed, positive relationships can allow species‐rich assemblages in which the species are more similar to each other than would be expected randomly (Gross 2008, Burns and Schmitt 2011, Sridhar et al 2012).…”
Section: Introductionmentioning
confidence: 99%